BAHASA ARAB MODERN DAN KONTEMPORER; KONTINUITAS DAN PERUBAHAN - Abd Aziz; Yuan Martina Dinata (Institut PTIQ Jakarta, 2019)
Modern Arabic has a distinction from classical Arabic in terms of lexical, phonological, morphological and syntactic. According to Abbâs al-Sûsah in Muhbib Abdul Wahab, Contemporary Arabic has the following characteristics: 1) accuracy of the use of Arabic at all levels: sound, morphology, syntax, and semantics; 2) more widely used in written language (al-Lughah al maktûbah) than oral language, 3) fluency and diversity-free 'amiyah, 4) standard language that is officially prepared. Based on observations of writers who try to classify modern Arabic vocabulary, the fields of religion, language and literature are the fields with the least development of modern Arabic vocabulary, when compared to economic, political, legal, psychological, health and other vocabularies. This may be due to the fact that from the fields of religion, language and literature there are not many new vocabulary terms, this may be due to religious, linguistic and literary norms.